Strategic decision making for a material construction store: A simple multi-attribute rating approach - Zuhdiyah Izzatun Nisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2025)
Purpose: TDJ Store, a leading building material retailer in Kendal, Central Java, has been operating its offline store for 15 years and its online store for two years. As part of its growth strategy, the store aims to transition to a company and open a new physical store. Research Methodology: To achieve this objective, a comprehensive strategy is required to ensure alignment with its goals. This study conducts an analysis of TDJ stores’ internal conditions and external environment to provide insights into the company's current situation. Utilizing Porter’s Five Forces framework, the Diamond Model, financial performance analysis, and SWOT analysis, this research examines both internal and external factors affecting TDJ stores. Results: The findings were then used to formulate strategies with the TOWS matrix and determine the type of strategy using the SPACE matrix, which identified an aggressive strategy (quadrant 1) as suitable. Finally, the SMART method is applied to prioritize alternative strategies, selecting market penetration as the most appropriate strategy for TDJ stores based on the current conditions, Conclusions: TDJ Store’s analysis shows an aggressive strategic position, with market penetration identified as the best strategy to enhance competitiveness through better management and marketing. Limitations: The study focuses on one SME with limited financial data, restricting generalization. Broader, data-rich studies are recommended. Contributions: This study integrates SWOT, TOWS, SPACE, and SMART methods, offering a practical framework for SMEs to develop sustainable, evidence-based growth strategies.